An investigation of the alternative futures of public libraries in 2030: a case study from the global South - Ali Zackery; Mohammad Mahdi Zolfagharzadeh; Elahe Ebrahimi Dorcheh (foresight, 2026)
Purpose Considering the importance and the long-standing role of Public Libraries (PLs) and the ever-increasing rate and intensity of socio-political, cultural and above all else technological changes, the future of PLs should be reimagined and their function and mission re-conceptualized. Although the alternative futures of PLs in the Global South could bear points of resemblance to those of the Global North, due to global mega-trends, relative socio-political homogeneity and technological convergence, local particularities could lead to divergent eventualities. This study aims to meet this objective. Design/methodology/approach Participatory action research and future-oriented action research (FAR) were deployed as our theoretical lenses. As for the method, Schwartzian steps of scenario-building were followed. A combination of social, technological, economic, environmental, political, value technique for horizon and environmental scanning; strengths, weaknesses, opportunities and threats (SWOT) analysis, foresight workshops, surveys and semistructured interviews was used to conduct this research. Findings In this research, the authors provide four scenarios of the future of PLs in Iran – as a case study in the Global South – in 2030. Participatory. The two key drivers of the future of PLs in Iran were chosen to be the conceptualization of PLs (service provider vs rhizome) and the essence of knowledge (consumptive vs experiential) which resulted in four scenarios: Co-LABoscope, Hubrary, Imitarium and Discoveria. Scenarios were quantified using speculations to provide a better comparison among these alternative scenarios and some strategic/tactical recommendations were made based on the initial SWOT analysis. Originality/value First, the multimethod case-studies using FAR are rare and this can be considered as one of the contributions of this research to the literature. Also, neologisms offered by the final scenarios can deconstruct and reconstruct how the future of PLs, in general, and education, in particular should be approached.